An Improved Photovoltaic Array Configuration for Photovoltaic System in the Presence of Maximum Power Point Tracking during Partial Shading Condition - K. Burhanudin; N.A. Kamarzaman; A.A.A. Samat; A.I. Tajudin; S.S. Ramli; N. Hidayat (Institute of Advanced Engineering and Science, 2017)
Power-Voltage (P-V) curve and Current-Voltage (I-V) curve determine the performance of the PV system. In this work, the arrangements of the PV module were reconstructed by adding the number of PV module in 3 strings configuration from 5 to 45. This method enhance the performance of the PV system as it able to show the characteristic of the P-V and I-V curve during partial shading and maximum irradiance despite higher number of PV panel. This study focuses on improving the PV array configuration and simulation speed of the PV panel. The simulation of small size PV array is possible, but the problem lies when the number of string and PV module used increases. New PV array configuration is flexible and easy to add string and increase the number of PV module. PV array configuration was modeled using MATLAB/SIMULINK software.